Resettlement, mental health, and coping: a mixed methods survey with recently resettled refugee parents in Canada - Amanda Sim; Eve Puffer; Afreen Ahmad; Lina Hammad; Katholiki Georgiades (BMC Public Health, 2023)
Abstract Background Resettlement experiences of refugee parents are under-researched despite evidence indicating higher risk of poor mental health. The current study integrates family systems and social determinants of refugee mental health frameworks to examine: (1) Refugee parents’ experiences of resettlement stressors and mental health; (2) Perceived impacts of resettlement stressors on individual and family indicators of well-being; and (3) Refugee parents’ coping strategies and resources. Methods The study draws on data from a mixed methods survey conducted with 40 Government-Assisted Refugee parents who had resettled to Hamilton, Canada within the past 4 years. Quantitative and qualitative data were analyzed separately and then integrated at the results stage using a weaving approach. Results Results indicate significant exposure to economic and social stressors across multiple domains of daily life, as well as high levels of parental psychological distress. Parents drew linkages between resettlement stressors and negative mental health impacts that were compounded by intersecting risk factors of ill health, caregiving burden, single parenthood, and low levels of education and literacy. Most parents rated themselves as coping well or very well and described various coping strategies such as positive reframing, problem solving, planning, and turning to religion. Quantitative and qualitative findings indicate high frequency of positive parent-child interaction and low frequency of family conflict, and highlight the importance of family as a protective resource for coping with adversity. Exploratory regression analyses suggest that longer stay in Canada, poorer self-rated health, higher levels of resettlement stressors, and more conflict between adults in the household may be associated with greater psychological distress. Conclusion Study findings highlight both the resilience of refugee parents and the psychological toll of navigating their families through a new and challenging environment. Policies and programs to provide comprehensive social and economic supports to refugees beyond the first one to two years after arrival are necessary to mitigate the mental health impacts of displacement over time and strengthen individual and family resilience. Such programs should include culturally responsive and family-based models of mental health care that acknowledge collective experiences and impacts of adversity, as well as harness family resources to overcome past and present challenges.